Bone and prosthetic component responses in various occlusal loading locations - Ishak, M. I. (Springer Verlag, 2013)
In this chapter, the data for equivalent von Mises stress (EQV) and resultant displacement within the bones and prosthetic components are presented and discussed numerically and also plotted in spectrum colouring scale. These indices are analysed for both intrasinus and extramaxillary approaches at different occlusal loading locations—central incisor (L1), 1st premolar (L2), 1st molar (L3) and 2nd molar (L4) regions. The resultant displacement magnitude was measured for the prosthetic components; framework and implants, owing to the difficulty of examining the direction of the framework and implants movement by merely looking at the stress results. Results showed that higher stress values were found within the bones and prosthetic components on working side for the extramaxillary as compared to the intrasinus approach, especially under the most posterior loading, L4 due to the cantilever effect. The prosthetic components in the extramaxillary also exhibited higher displacement magnitudes than those in the intrasinus when loading occurred in the anterior and the most posterior regions.